Role plays as a strategy to generate reflections about citizenship competences that allow conflict solving in an English conversation club. - Herrera Gómez, Daniel Andrés (Corporación Universitaria Minuto de Dios, 2020)
This research was conducted analyzing the application and knowledge about citizenship competences in skills that facilitate conflict solving in an extracurricular conversation club, through role plays representations as a pedagogical strategy that allowed interaction, dialogue and use of the communicative competence in English as foreign language. The research problem was identified initially at practicum level, where students had rude and conflictive behaviors, thus generating the interest to research about ways to create awareness about coexistence, avoiding fights and conflicts, dialoguing and being tolerant with each other, bearing in mind that the researcher was not aware that conflicts in classrooms can occur frequently, and can affect class dynamics and coexistence. Said that, the research problem was located at personal level, in a sense in which pre-service teachers might not be aware about conflicts between students, and therefore not knowing strategies and skills to facilitate solving conflicts
To analyze the articulation of citizenship competences and communicative competence in English to solve conflicts during role play representations and reflections generated by participants in a club conversation.
Keywords: Role play; Competences; Citizenship; Conflict solving; Juego; Competencias; Solución de conflictos